2018
DOI: 10.4236/aces.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Magnetic Dopant on the Structural and Electrical Properties in Superconducting YBaCu<sub>3</sub>O<sub>7-δ</sub> Ceramic

Abstract: The work reported in this paper aims at a better understanding of the magnetic doping effects on the structural and electrical properties for a series of YBa 2 (Cu 1−x Co x ) 3 O 7−δ ceramics. The Co doped YBa 2 Cu 3 O 7−δ are (YBCO) prepared by conventional solid state reaction method and characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM), differential thermal analysis (DTA) and resistivity measurements. The crystal lattice parameters are found to change due to the cobalt doping a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our results showed that the diffraction peaks increased in intensity for all TiO 2added samples, particularly at x = 0.4 wt.% TiO 2 concentration, with a noticeable shift of the peak position to the high angle, as presented in Figure 1b. This might be related to thermal cycle stress or the powder pelletising process [27].…”
Section: Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the diffraction peaks increased in intensity for all TiO 2added samples, particularly at x = 0.4 wt.% TiO 2 concentration, with a noticeable shift of the peak position to the high angle, as presented in Figure 1b. This might be related to thermal cycle stress or the powder pelletising process [27].…”
Section: Xrd Analysismentioning
confidence: 99%
“…Coatings 2023, 13, x FOR PEER REVIEW 4 of 12 a noticeable shift of the peak position to the high angle, as presented in Figure 1b. This might be related to thermal cycle stress or the powder pelletising process [27]. The variation of the lattice parameters a, b, and c with TiO2 concentration is shown in Table 1.…”
Section: Xrd Analysismentioning
confidence: 99%
“…Such phenomena included specific heat, critical field, tunneling, etc. The superconducting B-S-C-C-O has an orthorhombic structure [3], they consist of provskite copper oxide planes sandwiched between double bismuth oxide layers with rock salt coordination, and have been compared to the Aurivillins phase [4,5].This body-centered orthorhombic Braveries lattice is only an average structure, however as the compounds display incommensurate modulation [6]. In 1988 Meada et.…”
Section: Introductionmentioning
confidence: 99%